Teacher’s Code-Switching in the Teaching-Learning Process in 10th Grade of ESL Class - Simatupang, Lady Maysi Cahyani; Jismulatif; Indah Tri Purwanti (ETERNAL (English Teaching Journal), 2024)
Studying CS in ESL classrooms is significant as it can enhance understanding and facilitate communication between teachers and students. This study aims to analyze the types, functions, and students’ perception of code-switching (hereafter, CS) used by an English teacher at a private school in Pekanbaru, Riau to seek whether it is important to use CS in learning process for ESL students. The subjects of this study were an English teacher of ESL classes and 72 ESL students in the academic year of 2023/2024. This research employs a mixed-method approach with a qualitative descriptive design combined with the use of a questionnaire, which is suitable for capturing both the depth and breadth of the phenomenon. To identify the types and functions of CS, the researcher recorded the teacher’s utterances and distributed the questionnaire to get the students’ perception. The data were analyzed using Poplack’s (1980) three types of CS and Cahyani et al.’s (2016) four functions of CS. The results showed that the teacher’s most frequently used type of CS is intra-sentential CS. Additionally, the teacher employed CS to ensure students understand the instructions given. The students showed a positive perception of the teacher’s CS since it helped them understand and comprehend the classroom activities. These results highlight the importance of strategic CS in enhancing student comprehension and participation in ESL classrooms, suggesting broader implications for teaching practices in multilingual settings.